ANALISIS PERILAKU KONSUMEN DALAM KEPUTUSAN PEMBELIAN SEPEDA MOTOR PADA MAHASISWA SE-MALANG RAYA - Asna, Asna (Jurnal Ekonomi Modernisasi, 2010)
The development of motor vehicle industries especially motorcycle industries is an interesting phenomenon. Since the economic of Indonesia was declined, motorcyle industries indicated the improvment of sales. This research is trying to see the impact of the stimulus towards the customer purchase decision, when they buy motorcyle. It was sutdy on the University sudentsÂ  in Malang. The customer behavior is studied from the factors influencing that behavior, such as social, personal, psychological and cultural factors, whereas the customer purchase decision is studied from the decision making process, which is decided into fully planned purchases. The result of the research, which is taken from 100 respondents, shows that cultural, psychological and factors have positive influences sifnificantly towards the customer purchase decision. Whereas, from social and personal factors, it has no influences on the customer purchase decision.